Efforts to Improve Students' Problem-Solving Skills in Science Learning by Implementing the Problem-Based Learning Model in MIS Ni'matul Aziz - Depi Suhartini (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research aimed to investigate the efforts to improve students’ problem-solving skills in science learning through implementing the Problem-Based Learning (PBL) model at MIS Ni’matul Aziz. The study was conducted in the second semester of the 2025 academic year involving 30 students of class VII who were purposively selected as research participants. The research was implemented over two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using tests, observation sheets, student journals, and teacher reflection notes to measure improvements in students’ problem-solving skills. The problem-solving test consisted of five performance-based science questions aligned with the PBL phases: problem identification, hypothesis formulation, data analysis, solution design, and solution evaluation. Data analysis used both quantitative and qualitative techniques; quantitative data from pre-test, post-test cycle 1 and post-test cycle 2 were analyzed using descriptive statistics, while qualitative data from observations and reflections were analyzed thematically to support interpretation. The results showed that the implementation of the PBL model significantly improved students’ problem-solving skills. The average score increased from 51.2 in the pre-test to 68.5 in post-test cycle 1 and reached 82.7 in post-test cycle 2, indicating a progressive and statistically meaningful improvement. Furthermore, classroom observations documented increased student engagement, collaboration, and analytical reasoning during science learning activities. Teacher reflections also indicated that PBL enhanced students’ ability to identify scientific problems, analyze data, and communicate solutions effectively. The findings imply that PBL is an effective instructional model for enhancing problem-solving competencies in science learning contexts similar to MIS Ni’matul Aziz. The study recommends broader application of PBL in science curricula to cultivate higher-order thinking skills among learners.